Building text hierarchical structure by using confusion matrix - Yunbo Xiong (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
There are two strategies to build hierarchical structure of document category. One is hierarchical clustering and the other is confusion category. Based on confusion matrix of plane classifier, the paper made use of hierarchical classification to carry on experiments, and it is showed that the confusion category strategy was superior to hierarchical clustering strategy. And compared to plane classifier, confusion category strategy improved recall and precision of classification.